The usage of social network as a marketing tool: Malaysian Muslim consumers’ perspective - Sarwar, Abdullah Al-Mamun; Haque, A. K. M. Ahasanul; Yasmin, Farzana (Human Resource Management Academic Research Society, 2013)
The purpose of this study was to explore the buyer’ s opinion of using social networks as a marketing tool towards purchasing goods through onl ine in Malaysia. A total of 300 questionnaires were distributed to collect data. 27 8 valid questionnaires were received and used for further statistical analysis. This study r evealed that the variables, interaction in social network (time spend on social networking sites) and perception of security in purchasing goods online play the most significant role on the purcha sing preferences for Muslim consumers. The added value of this paper was to identify the link between theory and practice and identify the Muslim consumers’ purchasing decision through socia l networks.